Study the Effective Length of Quadrupole Magnet on Some Parameters of Ion Optical System from Plasma Source - Bushra J. Hussein (Genius Journals, 2023)
This study used a MATLAB program to investigate the impact of effective length (L mm) on the quadrupole magnet lens primary parameters, where values are selected (from 50 mm to 1000 mm), to determine the power of lens, focal length and displacement of both (horizontal and vertical) planes, respectively. Theoretical analysis was done as part of the study. Results indicated that the effective length was growing decreased the system's horizontal and vertical focal length, while for the power lens, increasing the effective length leads to an increase in its value for both the horizontal and vertical axes. Additionally, the longer effective length led to on a horizontal plane, a decreasing horizontal displacement (beam envelope), the opposite happens for the vertical axes
Keywords: Focusing lenses; Ion optical; A quadrupole magnet